Promoting sustainable resource use through product service systems. - Cook, M.; Angus, Andrew; Gottberg, Annika; Smith, Richard; Longhurst, Philip J. (Cranfield University, 2007)
In a world of declining prices for manufactured goods and increased global competition, many manufacturers have developed a range of services that complement and in certain instances replace traditional products, in an attempt to maintain or boost profitability. Resultant products have been classified as Product Service Systems (PSS) and comprise both an tangible artefact and intangible service, which are conflated through business processes to deliver value to customers. Research suggests that the environmental performance of PSS may be significantly better than that of traditional products. Theoretically, improvements in resource productivity that might be gained from use of PSS as opposed to traditional products are potentially enormous: somewhere between a factor of 10 and 20. To realise these environmental benefits, there is a need to identify instances where conventional material products can be substituted by PSS. This will depend on the criteria upon which consumers’ decisions are made. One prominent theory of decision-making assumes that a decision to buy is based on the performance of product or service against well-defined criteria, such as price and quality. An analytical technique is required to enable consideration of multi-criteria and provide information regarding the relative importance of each criterion. A review of the literature was undertaken to identify suitable methodologies for this study. Three techniques were identified as being appropriate, namely: Choice Experiments (CE); Multi-Attribute Utility Theory (MAUT); and the Analytical Hierarchy Process (AHP). AHP was seen to be a suitable tool to enable consumers to compare product service systems with traditional products and identify substitutions, as it is a robust method that is particularly suited to decisions made with limited informatio
Keywords: product service systems; multi criteria analysis; socio-economic